PROBABILISTICASSESSMENT AND FIELD TEST VERIFICATION FOR STRENGTH EVALUATION OF BRIDGE WITH DEFECTIVE GIRDER - Gebre, Abrham; Gebreyouhannes, Esayas; Gebre, Yisihak (Zede Journal of Ethiopian Engineers and Architects, 2023)
The use of high-quality materials, regular inspection and testing of constituent materials, appropriate curing processes, and an acceptable overall construction methodology are all required for bridge construction. Failure to handle the aforementioned ways causes the bridge to operate poorly, jeopardizing its load-carrying capacity. As a result, determining the load carrying capacity of the bridge and assessing its safety are critical. This study investigated the performance of a defective girder of a Reinforced Concrete (RC) bridge (located at km 69+937 along the Agulae-Berahle road segment) caused by failure of concrete to achieve the desired compressive strength. Various assessment methods were used to assess the strength of the existing defective girder. Following the uncertainty of random variables, a probabilistic assessment approach was used. A field load test was also used to correlate and verify the numerical result. The findings reveal that the bridge under investigation is safe against the design and legal loads specified in ERA Bridge Design Manual. Keywords: RC, deterministic approach, defective girder, probabilistic assessment, strength evaluation, uncertainty, random variables, load test